-3-(5-5p)=0

Simple and best practice solution for -3-(5-5p)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3-(5-5p)=0 equation:


Simplifying
-3 + -1(5 + -5p) = 0
-3 + (5 * -1 + -5p * -1) = 0
-3 + (-5 + 5p) = 0

Combine like terms: -3 + -5 = -8
-8 + 5p = 0

Solving
-8 + 5p = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '8' to each side of the equation.
-8 + 8 + 5p = 0 + 8

Combine like terms: -8 + 8 = 0
0 + 5p = 0 + 8
5p = 0 + 8

Combine like terms: 0 + 8 = 8
5p = 8

Divide each side by '5'.
p = 1.6

Simplifying
p = 1.6

See similar equations:

| -3(-2*x+4)-(x-6)=y | | f(m)=20-0.25m | | 69-5x=4x+18 | | 3y-10=5x+22 | | x^2=-13 | | -17x-20=-14x+70 | | -7/3(y-12)-1/6y=0 | | 3/4x-3/2=6 | | -7/3(y-12)-1/6y | | 4x+9=3x+17 | | 3x+7=2x+15 | | 5x^3/2-35=100 | | -177=9*n | | 11x-3=3x+21 | | 9x+18=27 | | 5x-35=100 | | 6x-5=31-2x | | 24-3x=56+2x | | 3x-4(7x+3)=5x+7(9x-10) | | 5.59+55.9=111.8 | | -17-(-40)=x/2 | | X=2(-2)+6 | | X*13-110=x*6-12 | | 5(5c-1)-3=23c+2 | | 3x/2+5=16x-11 | | 8w=4.2 | | 2/5n=24 | | 5-8x=92-29x | | -2k+3k-9+5k=0 | | 3/4*29/6 | | 6-10x=43x+17 | | 3(u+4)=(5+u)5 |

Equations solver categories